DETERMINAN PERSEPSI WAJIB PAJAK BADAN MENGENAI ETIKA PENGGELAPAN PAJAK (STUDI PADA WAJIB PAJAK BADAN YANG TERDAFTAR DI KANTOR PELAYANAN PAJAK PRATAMA PURWAKARTA) - Rivani Aulia Haq; Ayu Fury Puspita (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2019)
The aim of this study is to determine corporate taxpayers' perceptions on the ethics of tax evasion. This research was conducted at the Small Tax Office of Purwakarta. This study used primary data obtained through questionnaires submitted corporate taxpayers registered at the Small Tax Office of Purwakarta. The sampling method used in this study was convenience sampling. Hypothesis testing was conducted by the Partial Least Square (PLS) statistical method with the help of the SmartPLS program. Based on the correlation analysis, it was found that taxpayer compliance is at a low level (0.254673) and tax system is also at a low level (0.366459). Hypothesis testing found that, H0 rejected and Ha is accepted; this means that there is a relationship between taxpayer compliance and tax system, regarding corporate taxpayers' perceptions on the ethics of tax evasion.